Corrigendum to “Evaluating the climatic suitability of Engytatus passionarius Minghetti et al. (Heteroptera, Miridae) as a biological control agent of the invasive stinking passion flower Passiflora foetida L. in Australia through ecological niche models” [Biol. Control 191 (2024) 105461] - Minghetti, Eugenia (2024)
The authors regret to inform the Gorgon Barrow Island Net Conservation Benefits Fund was incorrectly acknowledged as supporters of this study. The authors would like to clarify this was done only as a courtesy because said organisation had in the past partially financed some of the field trips in which parts of the data used in this study were collected, not because they funded, participated, or were otherwise connected to this study, and wish to withdraw the acknowledgement in all versions of thispublication. The authors would like to apologise for any inconvenience caused.